2020
DOI: 10.1002/wsb.1122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lure on Detecting Mammals with Camera Traps

Abstract: Motion-triggered camera traps are subject to imperfect detection and thus camera-trapping surveys often try to increase species detectability as part of the study design. One possible way to increase detectability is to use lures, which may encourage a species to investigate a given area. Yet the effectiveness of lures is primarily grounded in anecdotal support. We quantified the effect of a common olfactory carnivore lure on the detectability of mammals near Chicago, Illinois, USA, during 27 August 2018-25 Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 37 publications
0
11
1
Order By: Relevance
“…To increase the detection probability of each species we placed one synthetic fatty acid scent lure in the camera line of sight, and lures were replaced on 2-week intervals if missing to remain consistent throughout the study. However, Fidino et al, 2020 later found that this type of lure has little to no effect on the detectability of most urban mammals. We used observation data collected between January 2017 and December 2018.…”
Section: Methodsmentioning
confidence: 99%
“…To increase the detection probability of each species we placed one synthetic fatty acid scent lure in the camera line of sight, and lures were replaced on 2-week intervals if missing to remain consistent throughout the study. However, Fidino et al, 2020 later found that this type of lure has little to no effect on the detectability of most urban mammals. We used observation data collected between January 2017 and December 2018.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, attractants could alter movements of animal, bringing them to areas where (Schlexer 2008;Holinda et al 2020): in turn, this could introduce sampling bias in some estimators, either for occupancy of for abundance (cf. Fidino et al 2020). Furthermore, the essence must be carefully selected because some lures could have different effects on both prey and predators, possibly decreasing their detectability (Fidino et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Their camera records were considered as independent events when consecutive images that contained the same species were recognizable as different individuals, a method used in several studies [60,64,68]. The use of lures is a widespread method in camera trapping, but optimizing the detectability of a target species can produce bias in calculating abundances, as the species behavior may be altered, or some species may be attracted whereas others may be repelled [88][89][90][91].…”
Section: Discussionmentioning
confidence: 99%